639. Indoleamine 2, 3 Dioxygenase, Age, and Chronic Immune Activation in HIV Patients. (26th November 2018) - Baer, Stephanie; Colombo, Rhonda; Johnson, Maribeth; Wakade, Sushama; Pacholczyk, Gabriela; Thompson, Stuart; Huang, Lei; Saag, Michael; Mellor, Andrew
Abstract: Background: Immune activation complicates HIV despite antiretroviral therapy (ART). Indoleamine 2, 3 dioxygenase (IDO) catabolizes tryptophan (T) to kynurenine (K), regulating immune activity. IDO activity increases in HIV patients and non-HIV patients with age. This study examines the relationship of IDO activity, bacterial translocation, and ageing in HIV patients on ART. We hypothesize that increased IDO activity caused by bacterial translocation is a factor in inflammation during aging. Methods. Samples and data from virologically suppressed HIV patients on ART in specific age strata were obtained from the Centers for AIDS Research Network of Integrated Clinical Systems. Samples and data from age and sex-matched healthy controls were obtained from the Multicenter AIDS Cohort Study and the Women's Interagency HIV Study. The ratio of K to T ( K / T ) and neopterin were used as indicators of inflammation; 16S ribosomal DNA (16S rDNA) and lipopolysaccharide (LPS) served as markers of bacterial translocation. Log transformation, chi-square tests, t -tests with Satterthwaite adjustment for continuous data, ANOVA, and ANCOVA homogeneity of slopes model were used. Results. Samples and data from 205 HIV patients and 99 matched controls were analyzed. HIV patients had higher K / T values across all ages. Younger HIV patients had greater K / T values than older healthy controls. Age, sex or race was not associated with differences in K / T . Current CD4 count or CD4 nadir had no association with K / T ratio. For HIV patients, there was an inverse relationship between LPS detection and K/T . For controls, there was no association between LPS and K/T . There was no association between PCR detection of 16S rDNA and K/T ratio in HIV patients or controls. Both groups had positive association between K/T ratio and neopterin. Conclusion. HIV patients have elevated K/T, even at younger ages, despite virologic control. The main hypothesis that K/T increases with advancing age was not supported in this cohort. Also, unlike other published literature, CD4 nadir, LPS, and 16S rDNA did not correlate with K/T ratio. This study suggests there may be an alternative driver of immune inflammation in well-controlled HIV patients other than bacterial translocation. Disclosures: A. Mellor, NewLink Genetics: Consultant, Consulting fee and Licensing agreement or royalty.